Competition between Imperata cylindrica and maize in the forest savannah transition zone of Nigeria - Chikoye, David; Ekeleme, F.; Lum, A.F.; Udensi, U.E. (Wiley, 2014)
operate cylindricais a noxious weed that infests annual and perennial crops in most tropical regions. High crop densities may offer opportunities to reduce. Cylindricacompetition in small-scale farming systems. The competitive ability of maize relative toI. cylindricawas evaluated in an addition series experiment in the forest savannah transition zone in 2006and 2007 at Ibadan, Nigeria. Maize andI. Cylindrica were planted in eight monoculture densities (4, 8, 12,16, 20, 32, 48 and 64 plants m 2) and in a 1:1 mixture at eight total densities (2:2, 4:4, 6:6, 8:8, 10:10, 16:16,24:24 and 32:32 maize: I. cylindricaplants m 2)asinmonoculture. Non-linear regression models were used to relate crop and weed shoot biomass to their density and total grain yield to maize density. In maize, intraspecific competition was more than interspecific competition; inI. cylindrica, interspecific competitionwas higher than intraspecific. As expected, total grainyield was lower in the mixture than in maize monocul-ture at all total densities. Average maize grain yield inmaize monoculture differed from that in mixtures by0.77 t ha 1in 2006 and 0.57 t ha 1in 2007. Niche differentiation indices were<1 in 2006 and>1 in 2007,indicating that both species competed for similar resources in 2006, but not in 2007. The greater com-petitive ability of maize overI. cylindricamay be associated with rapid growth and canopy development observed in the field.